1980
DOI: 10.1055/s-2007-1021714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of an Improved Magnifying Fiber-Colonoscope (FCS-ML II), with Special Reference to the Remission Features of Ulcerative Colitis

Abstract: We have adapted a new, high-performance magnifying fibercolonoscope (FCS-ML II) developed by Machida Industries, for clinical use. We have observed the remission process of ulcerative colitis with this new instrument and have compared our findings with those obtained by clinical examination, X-ray, ordinary gastroscope, and histologic examination of biopsy specimens. Our results show that the findings of magnifying fiber-colonoscopy correspond to those obtained with biopsy and histology, indicating that this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As for the observation of the fine mucosal structure in patients with ulcerative colitis, some studies have correlated the disarranged crypt openings and the degree of histologic inflammation. 8–13 In these studies, however, the stereomicroscope and fiberscope were used, and these are technically difficult to use routinely. Our use of the electric magnifying colonoscope, facilitated by the spraying of a 0.4% indigo carmine solution after standard colonoscopic observation, is an easy and convenient one‐touch operation, allowing observation of the fine structure of the colonic mucosa during routine examination.…”
Section: Discussionmentioning
confidence: 99%
“…As for the observation of the fine mucosal structure in patients with ulcerative colitis, some studies have correlated the disarranged crypt openings and the degree of histologic inflammation. 8–13 In these studies, however, the stereomicroscope and fiberscope were used, and these are technically difficult to use routinely. Our use of the electric magnifying colonoscope, facilitated by the spraying of a 0.4% indigo carmine solution after standard colonoscopic observation, is an easy and convenient one‐touch operation, allowing observation of the fine structure of the colonic mucosa during routine examination.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Hurlstone et al 31,32 reported on the efficacy of magnifying colonoscopy in UC using ''optical biopsy'' for the surveillance of colitic cancer and disease extent. Nishizawa et al 33 first reported the healing process patterns of UC mucosa using the feature of magnifying colonoscopy. Another study attempted to relate the features of magnifying colonoscopy to clinical and histological activity.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Endoscopic devices that include magnification have been recently developed, and attention has been drawn to the utility of a variety of minute findings that are achievable using magnifying observation. [8][9][10][11][12][13] However, few systematic comparisons between conventional and magnifying endoscopy have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, minimal disruption should be the goal during biopsy of IBD cases such as UC, where mucosae are particularly fragile. Endoscopic devices that include magnification have been recently developed, and attention has been drawn to the utility of a variety of minute findings that are achievable using magnifying observation 8–13 . However, few systematic comparisons between conventional and magnifying endoscopy have been reported.…”
Section: Discussionmentioning
confidence: 99%